2013
DOI: 10.1038/ismej.2013.168
|View full text |Cite
|
Sign up to set email alerts
|

Purine biosynthesis-deficient Burkholderia mutants are incapable of symbiotic accommodation in the stinkbug

Abstract: The Riptortus–Burkholderia symbiotic system represents a promising experimental model to study the molecular mechanisms involved in insect–bacterium symbiosis due to the availability of genetically manipulated Burkholderia symbiont. Using transposon mutagenesis screening, we found a symbiosis-deficient mutant that was able to colonize the host insect but failed to induce normal development of host’s symbiotic organ. The disrupted gene was identified as purL involved in purine biosynthesis. In vitro growth impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 44 publications
(48 reference statements)
0
55
0
Order By: Relevance
“…While we tried to find other candidates for the biofilm study, we have studied the purine biosynthesis-deficient mutants, the purL and purM strains (see Fig. S2 in the supplemental material), and found that these strains exhibit defects in biofilm formation that are independent of their auxotrophic growth (13). In other previous studies, purine nucleotide biosynthesis was shown to affect biofilm formation through the secondary messenger c-di-GMP, which plays a central role in the transition from a motile lifestyle to a biofilm lifestyle in Gram-negative bacteria (15,18,(27)(28)(29).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While we tried to find other candidates for the biofilm study, we have studied the purine biosynthesis-deficient mutants, the purL and purM strains (see Fig. S2 in the supplemental material), and found that these strains exhibit defects in biofilm formation that are independent of their auxotrophic growth (13). In other previous studies, purine nucleotide biosynthesis was shown to affect biofilm formation through the secondary messenger c-di-GMP, which plays a central role in the transition from a motile lifestyle to a biofilm lifestyle in Gram-negative bacteria (15,18,(27)(28)(29).…”
Section: Resultsmentioning
confidence: 99%
“…When the uppP gene of the Burkholderia symbiont, which is known to be involved in the biosynthesis of bacterial cell wall components, is mutated, the peptidoglycan integrity of the bacteria is weakened and the uppP mutant is unable to colonize the host midgut (12). When the purine nucleotide biosynthesis genes purL and purM are mutated, the mutants can colonize the host midgut but fail to reach a normal population level (13). When the bacterial polyhydroxyalkanoate (PHA) synthesis genes phaB and phaC are mutated, the PHA-deficient mutant strains are able to colonize and reach a normal population, but their population decreases in the later stages of symbiotic association, indicating that PHA is important for bacterial persistence in the host midgut (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The purM gene encodes an enzyme that catalyses the fifth step in the de novo biosynthesis of purines. Whilst there are no reports of any requirement for purine biosynthesis during bacterial intramacrophagic replication, it has been shown that purine biosynthesis-deficient mutants of Burkholderia, Sinorhizobium and Photorhabdus are defective in their ability to form symbiotic associations with insects, plants and nematodes, respectively (Ruisheng & Grewal, 2011;Buendía-Clavería et al, 2003;Kim et al, 2014). Moreover Pseudomonas aeruginosa must synthesize purines during both chronic and acute infections of animals (Turner et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Biofilms produced by crypt-associated exocellular Burkholderia spp. are detected in the crypt lumens of R. pedestris as an exocellular matrix with polysaccharides (52), and they are associated with host insect fitness (56). However, the nature of the biofilm, and the potential role it plays, in the Burkholderia-Blissus interaction is unknown.…”
Section: Discussionmentioning
confidence: 99%